Pengaruh Misfit antara Strategi Prospektor dan Sistem Pengendalian Manajemen terhadap Kinerja Perusahaan - Widyaningdyah, Agnes Utari; Setyaningtyas, Veneranda Atria (E-Jurnal Akuntansi, 2023)
Management Control System (MCS) is   closely   related   to   firm performance. This research to eximine the influence of misfit between prospector strategy with MCS on financial performance and non-financial performance. Financing company in East Java as a population research were registered in the   Financial Services Authority ( OJK) . Technique of sampling done by purposive sampling with criterion as managers of intermediate level and below. Questionnaires as data collection materials. First, identify misfit that residual of the prospector's strategy orientation and MCS. The hypotheses was tested by regression analysis. The outcome indicate misfit between prospector strategy and MCS had a positive effect on financial and non-financial performance. This is because financing institutions have their own regulations that are regulated by the OJK and BI, especially in terms of management control, with action and result control orientation. Keywords: Management Control System; Business Strategy; Misfit; Company Performance